Income and Price Elasticities of Food Demand (E-FooD) Dataset - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
The E-FooD Dataset provides income and price elasticities of food demand in developing countries. The elasticities are derived from food demand system estimations, using representative household survey data. The elasticities are available by income quintiles in rural and urban areas. The dataset will be updated periodically to include more countries and survey rounds.